2017
DOI: 10.6018/analesps.33.2.249811
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of detachment among university students: Validation of the Recovery Experience Questionnaire in educational contexts

Abstract: Título: La evaluación del distanciamiento psicológico (detachment) en estudiantes universitarios: Validación del Cuestionario de Experiencia de Recuperación en contextos educativos. Resumen: El objetivo de este estudio fue adaptar y validar el Cuestionario de Experiencias de Recuperación (Recovery Experience Questionnaire) para su uso en un contexto educativo. Hasta el momento, la evaluación del detachment o distanciamiento psicológico ha sido utilizada fundamentalmente en contextos laborales. El estudio tuvo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
2
8
0
2
Order By: Relevance
“…Although these results converge with the proposal by Sanz-Vergel et al ( 2010), studies carried out in other contexts have confirmed the structure of 16 elements; for example, the Argentine version for public and private sector workers (Trógolo et al, 2020), the Nepali format developed with nurses from university hospitals (Panthee et al, 2020), the version for Spanish university students (Merino-Tejedor et al, 2017) and the version for Japanese employees, although in the latter, a structure adjusted to 3 factors was initially identified, where psychological detachment and relaxation were condensed into a single factor (Shimazu et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although these results converge with the proposal by Sanz-Vergel et al ( 2010), studies carried out in other contexts have confirmed the structure of 16 elements; for example, the Argentine version for public and private sector workers (Trógolo et al, 2020), the Nepali format developed with nurses from university hospitals (Panthee et al, 2020), the version for Spanish university students (Merino-Tejedor et al, 2017) and the version for Japanese employees, although in the latter, a structure adjusted to 3 factors was initially identified, where psychological detachment and relaxation were condensed into a single factor (Shimazu et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…It should be noted that in the initial work by Sonnentag and Fritz (2007) work stress and control over work were considered as contrast variables, identifying the inverse relationship between time pressure and recovery experience; as well as between role ambiguity and situational limitations with psychological detachment and control over free time, and between overtime compliance with psychological detachment and relaxation. In other works, the recovery construct was inversely associated with negative affectivity and exhaustion and was positively associated with vigor, self-regulation, commitment, coping strategies, and certain personality dimensions (Merino-Tejedor et al, 2017;Trógolo et al, 2020).…”
Section: Discussionmentioning
confidence: 72%
“…The distinction between detachment with work and school may explain the negative relationship found. Previous research using the REQ in student populations found similar findings (Merino-Tejedor, 2017).…”
Section: Recovery Experiencessupporting
confidence: 66%
“…Differently from coping, recovery is a procedural, continuous experience that does not respond to a specific event, which would be the definition of coping. Previous studies have compared both constructs and found low or null correlations between them (Merino-Tejedor et al, 2017).…”
Section: Géneros -Multidisciplinary Journal Of Gendermentioning
confidence: 99%